Nipping diseases in the bud?: Ethical and social considerations of the concept of "disease interception" - Narchi, Jonas; Winkler, Eva C. (Public health ethics, 2021)
Abstract. ‘Disease interception’ describes the treatment of a disease in its clinically inapparent phase and is increasingly used in medical literature. However
Gesehen am 22.09.2021